Translation and linguistic strategies of English oxymora into Japanese by Japanese language learners - Musaev, Talaibek; Jamaluddin Aziz,; Jamila Mohd, (Penerbit Universiti Kebangsaan Malaysia, 2021)
An oxymoron is a complex term as it contains inherent contradictions. This often results in confusion and miscommunication. In translation studies, despite the existence of quite a rich body of research on figurative language, the dearth of research that focuses on oxymoron further compounds this complexity. The objectives of this research are two-fold. First, is identifying whether or not the Japanese language learners are aware of the existence of oxymoron, whereas the second objective is to determine strategies used in translating English oxymoron into Japanese. This study used written translation tasks and follow-up online interviews as the methods. The study utilises purposive sampling technique and the respondents are 12 undergraduate students from the Universiti Malaya majoring in Japanese Language and Linguistics. Six of the respondents are Malay and six are Chinese. The oxymora are taken from the corpus of English texts at english-corpora.org/iweb. Data were manually collected and analysed using Aixelá’s Culture-Specific Items classification as the framework for analysing translation strategies. The research found that the respondents have difficulties translating some English oxymora and the challenges lie in finding correct words to describe, if not similar oxymoron in the target language. Other than their existing knowledge, the respondents refer to online resources to help them with translation such as Google Translate and online dictionaries. However, with some unfamiliar oxymora, this strategy is insufficient as most online dictionaries directly translate figurative language. This study is intended to raise interest in the translation of oxymoron, because this topic is not often the subject of study and application in practice. This study will help language instructors in understanding the process of translation of oxymoron and in implementing this subject as a syllabus in the translation studies.